Biowaste-to-bioplastic (polyhydroxyalkanoates): Conversion technologies, strategies, challenges, and perspective - Bhatia, Shashi Kant; Otari, Sachin V.; Jeon, Jong Min; Gurav, Ranjit; Choi, Yong Keun; Bhatia, Ravi Kant; Pugazhendhi, Arivalagan; Kumar, Vinod; Rajesh Banu, J.; Yoon, Jeong Jun; Choi, Kwon Young; Yang, Yung Hun (Bioresource Technology, 2021)
Biowaste management is a challenging job as it is high in nutrient content and its disposal in open may cause a serious environmental and health risk. Traditional technologies such as landfill, bio-composting, and incineration are used for biowaste management. To gain revenue from biowaste researchers around the world focusing on the integration of biowaste management with other commercial products such as volatile fatty acids (VFA), biohydrogen, and bioplastic (polyhydroxyalkanoates (PHA)), etc. PHA production from various biowastes such as lignocellulosic biomass, municipal waste, waste cooking oils, biodiesel industry waste, and syngas has been reported successfully. Various nutrient factors i.e., carbon and nitrogen source concentration and availability of dissolved oxygen are crucial factors for PHA production. This review is an attempt to summarize the recent advancements in PHA production from various biowaste, its downstream processing, and other challenges that need to overcome making bioplastic an alternate for synthetic plastic.
Keywords: Biodiesel industry; Carbon and nitrogen; Commercial products; Conversion technology; Downstream-processing; Environmental and health risks; Polyhydroxyalkanoates; Synthetic plastics; Biomass; Bioreactors; Carbon; Fatty Acids, Volatile; Industrial Waste; Polyhydroxyalkanoates; Biodiesel waste; Bioplastic; Biowaste; Lignocellulosic biomass; Municipal waste; Polyhydroxyalkanoates